Perbandingan Pembentukan Gap Sensitivitas Pada Bank Syariah Mandiri (BSM) dan Bank Mega Periode 2011-2015 - Muhammad Wasiqul Firdaus Askarullah; Achsania Hendratmi (Universitas Airlangga, 2017)
Interest rate risk arise when there was a gap between assets and liabilities so the purpose of this study was to determine the position of the gap formed at Bank Syariah Mandiri (BSM) and Bank Mega and analyze the difference in the formation of gap based on the period of sensitivity ≤ 1 month, > 1-3 months, and > 3-12 months.This was a quantitative research with comparative study which uses sensitivity gap analysis to identify the position of the gap were formed and conduct the comparative analyzed with independent sample t-test and Mann-Whitney. The data being used was secondary data from Maturity Profile which contained in the Annual Financial Report of BSM and Bank Mega in the periods of 2011-2015.The results showed that in BSM, cumulatively, the formation of the gap in the periods of 2011-2015 was negative gap. Likewise at Bank Mega, the cumulative gap formation in the periods of 2011-2015 was negative gap. From the results of independent sample t-test and Mann-Whitney known that the formation of the gap in BSM and Bank Mega for a period of sensitivity of ≤ 1 month and> 1-3 months showed a significant difference, while the period of sensitivity> 3-12 months there was no difference significant.BSM suffered exposure to interest rate risk higher than the Bank Mega as the asset structure is dominated by Murabaha Financing (fixed rate) with long term (> 12 months) while liabilities dominated by Mudharabah Deposits (variable rate) with short-term (<12 months).